Evaluasi Pemberian Senanam Kaki Berbasis Video terhadap Peningkatan Sensitivitas Kaki Pasien Neuropati Diabetikum - Yunita Carolina Satti; Fransisco Irwandy; Federiko Woda Sado; Meliana Gau (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Diabetic Neuropathy is damage to the peripheral nervous system caused by microvascular damage due to chronic hyperglycemia. Treatment to reduce the risk of diabetic neuropathy, one of which is physical exercise. So physical exercise can be done at home, namely in the form of leg exercises. This study aims to compare the differences in foot sensitivity after being given newspaper foot exercises and foot exercises with a ball. Researchers used a quasi-experimental design method with a pre-test and post-test equal control group design approach. The research was carried out in the working area of the Cendrawasih Community Health Center, Makassar City. Sample selection in this research used the sampling technique used, namely Consecutive Sampling. The instrument in this study to measure foot sensitivity was 10 gr monofilament. The results of the analysis using the Mann Whitney Test showed that the mean rank value in the Football Foot Exercise Group was 10 and in the Newspaper Foot Exercise Group 16.5. There is a significant difference between the difference in increasing foot sensitivity in the Newspaper Foot Exercise Group and the Ball Foot Exercise Group. Where the average difference in increasing foot sensitivity in the Newspaper Foot Exercise group was greater than in the Ball Foot Exercise group. The results of the Mann Whitney test also showed 0.004 (p < 0.05), it can be concluded that there is a difference in the effectiveness of the Newspaper Foot Exercise Group and the Ball Foot Exercise Group in Patients with Diabetic Neuropathy